PASTORAL KONSELING BAGI PEMUDA YANG TIDAK AKTIF DALAM IBADAH MINGGU PAGI DI GMIST JEMAAT TORSINA WINANGUN - Kahuweka, Harjen (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2025)
This study discusses the pastoral counseling approach for young people who are not active in Sunday morning worship at the GMIST Torsina Winagun congregation. Pastoral counseling service is a task entrusted by God, if not carried out properly thenthis task will be entrusted to other. Second ther are many sheep who are lost or even abandoned and struging alone an over coming their problems. As shepered is remindedto pay attention to those who are marginalized in congregation. Third if not paid attention the sheep will be in danger or threatened . Therefore this pastoral counseling service is very much needed because it has a very impotant role in helping the congragatin aspecialy young people who are not active in Sunday morning worship at the Torsina Winangun Congregation.